THE ROLE OF DIGITAL-BASED ENTREPRENEURSHIP IN REDUCING THE UNEMPLOYMENT RATE: A LITERATURE REVIEW - Astrea Wulanda; Ritha F Dalimunthe; Prihatin Lumbanraja (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
In the era of growing digitalization, digital-based entrepreneurship has become one of the important solutions in addressing the rising unemployment rate. Technopreneurship creates opportunities for individuals to start new businesses in technology, such as startups and e- commerce, which can create new jobs. In addition, technopreneurship also encourages technological innovation, both in product and service development, which can open up new opportunities to create jobs in technologically emerging sectors. The research method used involves analyzing the literature to highlight the contribution of digital entrepreneurship in creating new job opportunities and expanding market access for workers. The results show that digital entrepreneurship has great potential to reduce unemployment rates by facilitating creativity, innovation and economic engagement at both local and global levels. Policy implications and suggestions for further development are also discussed in this abstract.